Reconsidering the tradition: the Odinic hero as saga protagonist - Matveeva, Elizaveta (2016)
The purpose of this thesis is to evaluate and reconceive the scholarly understanding of one of Óðinn’s aspects – Óðinn as a patron to a mortal hero figure. This theme runs through a number of Old Icelandic and continental Scandinavian texts, but it is most widely represented in the fornaldarsaga genre. To formalise the discussion as well as the choice of material, the concept of the Odinic hero complex was introduced, which encompasses narrative structures, imagery and other material associated in the sagas with a protagonist helped and betrayed by Óðinn. This Odinic hero narrative has been looked at on the example of three fornaldarsǫgur, Vǫlsunga saga, Hrólfs saga kraka and Gautreks saga, as well as learned Latin texts connected to saga literature. The analysis also relied on the evidence of saga narratives that do not explicitly demonstrate the complete Odinic hero complex, but contains significant thematic parallelism to the main sources; these secondary sources included Hálfs saga ok hálfsrekka, Ǫrvar-Odds saga and Hervarar saga ok Heiðreks. The findings support the notion that a number of historians of religion have proposed, that there is a clear structural connection between the Odinic hero paradigm, initiation sequences and the themes of berserkir and shapeshifting. On the other hand, the dissertation shows that this thematic unity is in many cases a younger phenomenon than usually proposed, which leads to the necessity to re-evaluate a number of fornaldarsǫgur as sources on Old Scandinavian mythology and read them from a different perspective.